Effect of saliva of patients with leukemia on surface hardness and roughness of enamel and dental composite resin during chemotherapy regimen: An – Invitro study - Muhyaddin Aziz , Nsar; Hassan Hamza, Hiwa (Diyala Journal of Medicine, 2023)
Background: Evaluate the surface roughness and hardness of tooth enamel and dental resin composite restoration immersed into saliva collected from leukemia patient. Objective: To evaluate the surface roughness and hardness of tooth enamel and dental resin composite restoration immersed on to saliva collected from 4 types of leukemia patient. Patients and Methods: 30 patients with 4 types of leukemia (Acute lymphoblastic leukemia ALL, Acute myeloid leukemia AML, Chronic lymphocytic leukemia CLL, and Chronic myeloid leukemia CML) were included for taking saliva separately. A total number of 50 enamel specimen and 50 of composite resin disk were prepared and randomly divided into 5 groups of enamel (1,2,3,4, and 5) and 5 groups of composite resin disk (A,B,C,D, and E), surface roughness and hardness were measured and data collected, group A and 1 were immersed in artificial saliva for 7 days as control, group B and 2 immersed into saliva collected from patient with ALL, group C and 3 immersed into saliva collected from patient with AML, group D and 4 immersed into saliva collected from patient with CLL and group E and 5 immersed into saliva collected from patient with CML all group for 7 days then surface roughness and hardness were measured data collected and analyzed and statistically significant regarded at p<0.05. Results: In group A and 1 artificial saliva there were no significant effect on surface roughness and hardness of both enamel and composite resin disk, while surface roughness and hardness of enamel and composite resin significantly changed after immersing in saliva of ALL, AML, CLL, patients and surface roughness of composite resin highly significantly increased after immersing in saliva of CML patients. Conclusion: Saliva of ALL, AML, CLL, and CML seems to significantly changes in mechanical properties of enamel and composite, however saliva of CML highly significantly increase surface roughness of composite resin.